2018
DOI: 10.1002/ar.23981
|View full text |Cite
|
Sign up to set email alerts
|

Sound Generating Structures of the Humpback Dolphin Sousa plumbea (Cuvier, 1829) and the Directionality in Dolphin Sounds

Abstract: The macroscopic morphology of structures involved in sound generation in the Indian Ocean humpback dolphin (Sousa plumbea) were described for the first time using computed tomography imaging and standard gross dissection techniques. The Indian Ocean humpback dolphin may represent a useful comparative model to the bottlenose dolphin (Tursiops sp.) to provide insights into the functional anatomy of the sound production in dolphins, since these coastal dolphins exhibit similar body size and share similarities on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The late transformation of the rostrum might reflect shifts in the feeding and/or behavioural (acoustic) patterns of these species (Plön et al, 2015;Troina et al, 2016) and potentially indicate higher vulnerability when facing a changing environment. Young individuals of coastal NBHF species and S. plumbea (i.e., mainly male adolescents) seem to be more susceptible to die in gill nets (Atkins et al, 2013;Reeves et al, 2013) and this might be related to, among other things, the late development of an important structure to modulate biosonar clicks (i.e., rostrum) (Song et al, 2016) and their restricted field of perception compared to other coastal forms such as T. gephyreus (Frainer et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The late transformation of the rostrum might reflect shifts in the feeding and/or behavioural (acoustic) patterns of these species (Plön et al, 2015;Troina et al, 2016) and potentially indicate higher vulnerability when facing a changing environment. Young individuals of coastal NBHF species and S. plumbea (i.e., mainly male adolescents) seem to be more susceptible to die in gill nets (Atkins et al, 2013;Reeves et al, 2013) and this might be related to, among other things, the late development of an important structure to modulate biosonar clicks (i.e., rostrum) (Song et al, 2016) and their restricted field of perception compared to other coastal forms such as T. gephyreus (Frainer et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…plumbea (i.e., mainly male adolescents) seem to be more susceptible to die in gill nets (Atkins et al, 2013; Reeves et al, 2013) and this might be related to, among other things, the late development of an important structure to modulate biosonar clicks (i.e., rostrum) (Song et al, 2016) and their restricted field of perception compared to other coastal forms such as T . gephyreus (Frainer et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the animal communication, the pronunciation is not only depending on a series of pronounced organ coordination work [40][41][42], but also depending on the control of central nervous system [43]. The animals have been adapted to the environment after a long time evolution process via a series of successful constructed conditional reflexes [44].…”
Section: Discussionmentioning
confidence: 99%
“…The epicranial or nasal complex of dolphins have a lip‐like valve at the nasal passage called monkey‐lips, which given air pressure and interaction with the skull, melon, and air sacs can produce directional sound beams (Frainer, Plön, Serpa, Moreno, & Huggenberger, 2018). Mead (1975) examined the nasal passages and diverticula in Stenella , and showed that the premaxillary sac in Stenella was quite uniform in the species examined and was like that of Tursiops truncatus .…”
Section: Figurementioning
confidence: 99%